Numerical research on the impact of horizontal freezing on existing underground structures in shield reception - Hong, Zequn; Fu, Shuoren; Wu, Yuanhao; Zhang, Yong; Lu, Lu (Frontiers in Earth Science, 2025)
The freezing construction of the end of the new shield tunnel has a mechanical impact on the surrounding structures. Few studies exist on the reasonable range of soil reinforcement near the shield tunnel and the influence of frost heave on the existing structure during the freezing process. To explore the influence of horizontal freezing of a proposed tunnel on existing underground structures, a three-dimensional numerical model of ‘thermal-mechanical’ coupling was established based on the horizontal freezing reinforcement project applied in a shield receiving end, and the temperature field distribution characteristics of different freezing stages were obtained. After confirming that the frozen wall had reached the design thickness based on the temperature field, the mechanical effects of frost heave on the existing structures were investigated, including the side tunnel, the upper subway tunnel, and the end diaphragm wall. The results showed that the frost heave pressure was mainly distributed in the structure near the freezing zone, while the structure far away from the freezing zone was relatively less affected by frost heave. By defining the strong and weak influence sections, we introduced the influence coefficient η to quantify the frost heave effect on the side tunnel. Under the condition that the thickness of the frozen wall was constant, the strong influence range of the side tunnel reached 1.4 times the freezing length of the proposed tunnel at a distance of 3.6 times the frozen wall thickness. The farther the clearance between the side tunnel and the proposed tunnel was, the smaller the influence coefficient η was, and the shorter the strong influence section was. The frost-heaving effect generated by freezing at the shield tunnel receiving end was more pronounced along the diameter of the freezing pipes, while axial release strength was comparatively weaker. This research can provide a reference for evaluating the influence of freezing construction on adjacent underground structures.